The Improvement of Critical Thinking Skill And Concept Mastery Through Problem Based Learning Using The Strategy Of Mind-Map On Ecosystem Lesson - Tia Ghozwatul Fikriyah; Yossa Istiadi; Didit Ardianto (JSEP (Journal of Science Education and Practice), 2020)
This research aims to improve the concept mastery and critical thinking skill of students on the lesson of ecosystem. The method used in this research was quasi-experimentalal with Pre-post test only design. This research was conducted at Islamic Senior High Scholl (Madrasah Aliyah) in Karawang District. There were total 40 objects in both control and experimentalal class. The instruments used are essay, multiple choices test, questionnaire, and observation. The result of this research shows that the using of Problem-Based Learning model with Mind-Map strategy has an average score of 80 in concept mastery and 75 in critical thinking skill. The research shows that the N-gain of critical thinking skill in experimentalal class was 68 (middle criteria), meanwhile the N-gain of concept mastery was 78 (high criteria) and the respond in this class was more enthusiastic. The students’ activity in the class after being observed was improved since the students could understand the lesson more properly. This shows that Problem-Based Learning with Ming Map strategy can improve critical thinking skill and concept mastery.